Indigenous peoples, national parks, and protected areas : a new paradigm linking conservation, culture, and rights - Stevens, Stan (University of Arizona Press, 2014)
""This passionate, well-researched book makes a compelling case for a paradigm shift in conservation practice. It explores new policies and practices, which offer alternatives to exclusionary, uninhabited national parks and wilderness areas and make possible new kinds of protected areas that recognize Indigenous peoples' rights and benefit from their knowledge and conservation contributions"--Provided by publisher"--